Why they persist? An analysis of dual class structures and the unification process in the U.S. and Brazil - Gabriela M. Engler Pinto (Revista Direito GV)
The unbundling of cash flow and voting rights has been severely criticized worldwide and yet, the dual class structure persists as an alternative widely adopted by firms. This paper aims to provide some explanations as to why this happens, particularly from a comparative perspective that analyzes the contexts of Brazil and the United States, two countries that take a rather different approach regarding corporate ownership structures. In order to do so, it reviews the panorama of dual class structures, their main characteristics and the unification process that both countries underwent. On top of these discussions, this paper presents some arguments to explain why the dual class structure still persists both in Brazil and in the U.S. (although with variable intensity), despite all the criticism aimed at the segregation of cash flow and voting rights.